Media business and political business: The Struggle for power towards the 2014 Presidential election in Indonesia - Ludiro Madu (Jurnal Ilmu Komunikasi, 2016)
The 2014 presidential election has interestingly attracted the interest of several business people to participate in the struggle for presidential power in Indonesia. Jusuf Kalla, Aburizal Bakrie, Harry Tanusudibyo, and Surya Paloh are the examples of those business people who will potentially run for the 2014 presidential candidacy. This paper assumes that the increasing interest of business people in politics is due to the failure of post-1998 democratization in effecting new regulations for the involvement of business people in the political arena. While recent democratization has not allowed the participation of military personnel in politics, the post-1998 democratic structure has built new political opportunity for business people to become politicians. With special reference to Indonesia’s big business in media, this paper seeks to scrutinize the nexus between big business and politicians in their efforts to dominate the media be it printed, electronic, and online. Using the approach of the link between business and democracy, this development points to the formation of political and media oligarchies which have centered around certain business individuals and politicians as the preparation for their involvement in the 2014 presidential election. Additionally, analysis on the previous 2004 and 2009 presidential elections are of importance as well in providing the continuation and break-up of coalition patterns among big businesses or conglomerates and politicians. Finally, this paper argues that democratization has increased political opportunity for big businesses in using their media control and ownership for building coalitions with politicians in their quest to capture power in the 2014 presidential elections in Indonesia.